Correlation between physical, technical and tactical dimensions in under-20 category football players - Patrick Alan de Souza Pfeiffer; Júlio César Gomes da Silva; Eric de Lucena Barbosa; Rodrigo Wanderley de Sousa-Cruz; Luciano de Oliveira; Rodrigo Benevides Ceriani; Gilmário Ricarte Batista (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: presentation of the topic (maximum two key sentences).